Emerging e-collaboration concepts and applications - Kock, Ned F., 1964- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This book presents a state-of-the-art discussion of conceptual and applied e-collaboration issues. Business organizations increasingly rely on collaborative processes to maintain their competitiveness. E-collaboration technologies are at the source of something that underlies most business, political, and even societal developments - intense human collaboration"--Provided by publisher.